Implementation of Writing, Talaqqi, Tarjim, and Takrir Methods In The Process of Memorizing The Qur'an At Pesantren Ayatur Rahman Cerme Gresik - Maziyah, Alif; Amirudin, Noor (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
The Qur'an is the word of Allah that was revealed to the Prophet Muhammad through the Angel Gabriel (peace be upon him). The Qur'an is the most sublime dhikr from the all-wise Rabb, the Qur'an is a real light, a cure for the disease that is in the chest, and guidance and mercy for believers [Majdi Ubaid, 2014]. While memorizing the Qur'an is one of the efforts to protect the verses of Allah SWT, memorizing it makes humans always guided in living the life of the world even in the hereafter will get salvation or intercession. Memorizing the Qur'an is an effort to string letter by letter, verse by verse letter by letter in the Qur'an. The memorizers of the Qur'an have various ways of doing the process of memorizing the Qur'an. The difference in the method of memorizing the Qur'an is none other than because of the different ways of learning for each human being, some tend to listen first or auditory, and some are visual, namely by reading many times. Therefore, as one of the final assignments of the lecture, we conducted research at the Ayatur Rahman Qur'anic Boarding School in Cerme-Gresik. This type of research is qualitative with interview, observation, and documentation methods. The results of the author's research show that the method used at the Ayatur Rahman Qur'anic Boarding School in Gresik consists of four methods, namely Talaqqi, writing method, tarjim method, and Takrir method